1995
DOI: 10.1126/science.270.5234.299
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Shigella as a DNA Delivery Vehicle for DNA-Mediated Immunization

Abstract: Direct inoculation of DNA, in the form of purified bacterial plasmids that are unable to replicate in mammalian cells but are able to direct cell synthesis of foreign proteins, is being explored as an approach to vaccine development. Here, a highly attenuated Shigella vector invaded mammalian cells and delivered such plasmids into the cytoplasm of cells, and subsequent production of functional foreign protein was measured. Because this Shigella vector was designed to deliver DNA to colonic mucosa, the method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
122
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(124 citation statements)
references
References 22 publications
1
122
1
Order By: Relevance
“…[1][2][3] It has been shown that bacteria, which have evolved the ability to enter mammalian cells, are able to transfer genetic material to host cells without major DNA rearrangements occurring during the transkingdom transfer process. [4][5][6] Attenuated Salmonella strains have been successfully used as a carrier system for the in vivo delivery of nucleic acid-based vaccines. 7 This approach has proven to be efficacious in protecting against infectious diseases and for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It has been shown that bacteria, which have evolved the ability to enter mammalian cells, are able to transfer genetic material to host cells without major DNA rearrangements occurring during the transkingdom transfer process. [4][5][6] Attenuated Salmonella strains have been successfully used as a carrier system for the in vivo delivery of nucleic acid-based vaccines. 7 This approach has proven to be efficacious in protecting against infectious diseases and for cancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuated mutant strains of Shigella flexneri, Salmonella typhimurium as well as invasive E. coli and L. monocytogenes can successfully transfer in vitro plasmid DNA to a wide range of rodents and primate cell lines as well as dendritic cells. [12][13][14][15][16] So far, the ability of Shigella and Salmonella to target dendritic cells has been mainly exploited to develop DNA vaccines. 12,15,32 However, more recently, invasive bacteria have been used also as DNA vectors to correct inherited genetic defects in somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] So far, the ability of Shigella and Salmonella to target dendritic cells has been mainly exploited to develop DNA vaccines. 12,15,32 However, more recently, invasive bacteria have been used also as DNA vectors to correct inherited genetic defects in somatic cells. Administration to genetically immunodeficient mice of avirulent Salmonella bearing murine IFN-g gene resulted in transgene expression within macrophages and dendritic cells, correction of the genetic defect, and restoration of the cellular phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one of the major concerns regarding the use of bacterial vectors particularly those derived from attenuated strains is the stability of the recombinant phenotype and the potential reversion to full virulence [101]. In addition, although a number of bacterial vectors [34,37,93,133,147,148,151]. Although significant progress has been made in developing and evaluating bacterial vectors for inducing protective immune responses, there are not many reports of their application to vaccinate veterinary species (Tab.…”
Section: Bacterial Vectorsmentioning
confidence: 99%